The Impact of Health Shocks and Gender on Labor Force Participation: Longitudinal Evidence from Indonesia - Febrian, Febrian (Global Economic, Social, and Development Review, 2025)
This study investigates the relationship between health dynamics and labor force participation (LFP) in Indonesia, utilizing nationally representative panel data from the Indonesia Family Life Survey (Waves 3–5, 2000–2014). Employing fixed-effects and random-effects logistic regression models, we analyze the impact of health status and health shocks on LFP and examine the moderating roles of wealth and gender in this relationship. Key findings reveal a significant health premium, but one that is unequally distributed: good health increases the probability of LFP by 39.8 percentage points for men but only 15.1 percentage points for women, underscoring substantial gendered constraints. Furthermore, health shocks reduce LFP by approximately 55%, yet household wealth alone fails to buffer this negative effect. Urban-rural disparities in the health-LFP link are statistically insignificant, indicating that vulnerability is geographically widespread. Collectively, these results challenge the sufficiency of traditional coping mechanisms and underscore the urgent need for proactive, gender-sensitive social protection policies designed to mitigate health-related productivity losses. This research advances human capital theory by quantifying the gendered returns to health and the limitations of passive wealth buffers, providing an empirical foundation for targeted policy innovation in Indonesia.